Headaches and their relationships to Covid-19 (Research, Society and Development, 2022)
Covid-19 is an infectious disease caused by the SARS-CoV-2 coronavirus, which reached a pandemic stage in 2020, due to its high transmissibility, in addition to being asymptomatic or even reaching a picture of respiratory failure, and not rely on specific treatment. The objective of the research is to study the characteristics and prevalence of headache caused by Covid-19, comparing its characteristics, through an exploratory research with post-Covid-19 patients (online forms formulated via Google Forms with semiological and epidemiological characteristics with disclosure through social networks) and also descriptive (research in books and articles about the clinical, epidemiological characteristics and treatments of post-Covid-19 headache), which aims to collect enough data for an analysis and clinical comparison of headaches with different etiologies, performed through of spreadsheets and graphs. The study obtained 68 responses consistent with the questionnaire, with this we identified a more typical profile of patients in relation to the headache symptom associated with Covid-19, with female hegemony, with most not believing to have contracted the Ômicron variant. But with the headache being gradual during the infection, predominantly located anteriorly, lasting more than 1 day, with moderate to severe intensity, with recurrent episodes on the same day, being constant in appearance, with the condition ameliorated in recent months, improving mainly with medication and worsening with movements, in addition to being associated mainly with respiratory and gastric symptoms.